Strategy for Utilizing Household Organic Waste as Compost Using Fishbone Diagram and SWOT Analysis During Covid-19 Pandemic - Manggi Dwi Cahyono; Nurmawati Nurmawati; Mochammad Hatta (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: To maximize the processing of organic waste into compost that is useful for the surrounding community and to find out the cause of the slow processing of waste in Bambe village. Design/methodology/approach: The method used in this research is Fishbone Methods and SWOT Analisys. Findings: The main obstacles to poor organic waste management are the lack of knowledge of Bambe village residents in sorting organic and inorganic waste, unavailability of supporting equipment in managing organic waste into compost, lack of TPS-T places and facilities, inadequate waste processing officers, lack of support from the local government. so that the funding factor from the APBN and the provincial APBD is a problem that can hinder the process of processing organic waste. Research limitations/implications: Can optimize the use of house hold waste in the form of organic waste into compost. Practical implications: The use of house hold waste that can be converted into compost will reduce the amount of existing waste. Originality/value: Socialization of the use of processing and addition of waste processing facilities to residents is very useful for solving existing problems and the local government must be willing to support it in terms of funding so that the waste processing process becomes better. Paper type: Research paper